Reform and counter-reform of primary education during the Second Spanish Republic and the rise of the fascism (1932-1943) - Bonito, Justo Cuño (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
In the traditional clash between The two Spains, the most mellow and conservative traditionalist Spain ended up by imposing its domain over the freethinker Spain once again. The attempt to have a comprehensive reform of the educational system as an essential step for a deep social transformation, launched by the Second Spanish Republic, just failing by the reluctance of the church and more conservative elites, before any modification of social setting. Perhaps, as a result of this perennial conflict, the current education system lacks a stable and constantly model redesign pormor [AT1] , not its efficiency, conceptual and methodological developments and breadth of view, but ideological by the difficulties of the two major parties or by the desire for survival and perpetuity of the ministry of that epoch.